Analisis Kemampuan Mengubah Pronomina (Isim Dhomir) Mahasiswa Semester I B Akhwat STIT Darul Fattah Bandar Lampung: Analisis Kemampuan Mengubah Pronomina (Isim Dhomir) - Muhammad Zaky Sya’bani (An Naba, 2020)
This research departs from the problem of students who feel difficulties in understanding the basic concept of change pronoun in Arabic either connected or separate words. While the research object is students level 1B female STIT Darul Fattah central of Lampung which amounted to 18 students with qualitative descriptive research model. Researchers collect data through observations, interviews, documentation and tests while the validation technique used is data triangulation. The results of the research have been done stating that the ability of students level 1B female in understanding the basic concept of change pronoun is still relatively low are caused by multiple internal and external factors of a diverse student. It is evidenced by only 5 out of 18 students who get the value of > 80 whereas 13 others get < 80. Then researchers offer several solutions according to the problems faced by students so that students can be easier in understanding the basic concept of changes pronoun and able to apply it in Arabic speaking conversations and texts in Arabic.